PENGARUH SISTEM INFORMASI AKADEMIK (SIAKAD) DAN KUALITAS PELAYANAN ADMINISTRASI TERHADAP KEPUASAN MAHASISWA - Wa Ode Trinor Hayati; ALida Palilati; Endro Sukotjo (Pascasarjana Universitas Halu Oleo, 2018)
This study aims to determine and analyze the effect of academic information systems and the quality of administrative services on student satisfaction in the Halu Oleo University Faculty of Mathematics and Natural Sciences. The population in this study were all students from 2014 to 2016, with a sample of 93 respondents. Hypothesis testing is done by using multiple regression analysis. The results showed that academic information systems and administrative service quality simultaneously and partially had a significant effect on student satisfaction.Keywords: academic information system, quality of administrative services, student satisfaction